PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION SEBAGAI UPAYA PENINGKATAN KETERAMPILAN MENULIS - Novita Fitri Amin (Ulumuna: Jurnal Studi Keilsman, 2017)
Writing in anability to use a language in communicate involves a language written based on linguistic style excert that, writing has to be done effectively, because writing as productive activity and expressive the reseacther formulates some problems such as 1)how students activity in writing a narrative text using group investigation at class X-2 MAN Jungcangcang pamekasan 2) how students respose after writing narrative text by using this method 3) how increasing of class X-2. Based on date analysis, we know that students activity in using this method as the willy how to increase writing skill in narrative text based on the quantity of students activity include added category (3.10) the students are active. From the analysis therough questionnaire about students mereinse states “yes” 69,38% compare students who says “no” the percentase of 22,24% and the persentase of “sometimes” 19,04% and the persentase of students who say “yes” ≥ 60% it show that students respond is “positive” but the percentase of achievement classicall 73,80% bligger than quality “not achieve” 9,52%, so the method can be said “achieved”. The result between students before give this method 7,14% after they are given this method increase 64,28%.